THE AGENCY AGREEMENT IN THE NEW CIVIL CODE - Livia MOCANU (Challenges of the Knowledge Society)
Although not for the first time, the new Civil Code regulated separately the agency agreement in art. 2072 - 2095. As a consequence of the monist concept, the new Civil Code includes many agreements from now on, including those considered up to present proper to the commercial activity. It is also the case of the agency agreement, previously regulated by a special normative document that is Law no. 509/2002, based on a Directive of the European Union. The rules comprised in the present regulation define a separate agreement, stand-alone agreement, with its own features, in agreement with the part it plays in achieving the intermediation activity, a part legally established by the law of the European Union. The present study is focused on the analysis of the legal regime of the agency agreement, in accordance with the new Civil Code, dealing with the following aspects: its legal frame, its legal definition and features, the content of the agreement, its effects and the termination of the agency agreement.